In-situ vibrational spectroscopic observation for thermally activated structural changes of 100% cellulose nanofiber molding with ultralow friction - Okubo, Hikaru; Ishikawa, Tomori; Hashiba, Hiromi; Inamochi, Toru; Nakano, Ken (Frontiers in Mechanical Engineering, 2024)
This paper reports the thermally activated ultralow friction of 100% cellulose nanofiber (CNF) molding. The mechanism of friction reduction was investigated using a laboratory-built in-situ Raman tribometer. Our experimental results showed that a CNF molding exhibited an ultralow friction coefficient of below 0.04 in a CNF ring and steel disk tribopair under high-temperature conditions (T >100 °C). The results of the temperature-rise friction test showed that the friction coefficient of the CNF molding strongly depended on the temperature and decreased linearly with increasing temperature. The in situ tribo-Raman monitoring results, during friction, indicated a change in the structure of the CNF molding. Therefore, the crystallinity indices and lengths of the CNF fibers gradually changed as the temperature increased. Moreover, transfer tribofilms were observed on the counter-steel surface against the CNF rings. When the CNF molding exhibited thermally activated ultralow friction, the tribofilm was mainly composed of cellulose and graphitic carbon. Our results suggest that the thermal and friction-activated structural transformations of CNF molding and CNF-derived transfer film formation are pivotal factors contributing to the ultralow friction phenomenon observed in CNF molding at high temperatures.